2022
DOI: 10.1101/2022.12.09.519809
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Computing Absolute Binding Affinities by Streamlined Alchemical Free Energy Perturbation (SAFEP)

Abstract: Free Energy Perturbation (FEP) is a powerful but challenging computational technique for estimating differences in free energy between two or more states. This document is intended both as a tutorial and as an adaptable protocol for computing free energies of binding using free energy perturbations in NAMD. We present the Streamlined Alchemical Free Energy Perturbation (SAFEP) framework. SAFEP shifts the computational frame of reference from the ligand to the binding site itself. This both simplifies the therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…By moving away from the six anchor points of the VBA, this was intended to simplify the selection of stable and efficient restraints. The “distance to bound configuration” (DBC) restraint is also intended to simplify restraint selection and to minimize the variance of free energy estimates for removing the ligand’s intermolecular interactions. This is achieved by directly restraining the RMSD of a subset of the ligand coordinates within the frame of reference of the binding site in order to optimally restrict the accessible configurational volume as the ligand intermolecular interactions are removed. However, because this scheme couples the internal and external degrees of freedom of the protein and ligand, there is no simple way to calculate the free energy of releasing the noninteracting ligand to the standard state.…”
Section: Introductionmentioning
confidence: 99%
“…By moving away from the six anchor points of the VBA, this was intended to simplify the selection of stable and efficient restraints. The “distance to bound configuration” (DBC) restraint is also intended to simplify restraint selection and to minimize the variance of free energy estimates for removing the ligand’s intermolecular interactions. This is achieved by directly restraining the RMSD of a subset of the ligand coordinates within the frame of reference of the binding site in order to optimally restrict the accessible configurational volume as the ligand intermolecular interactions are removed. However, because this scheme couples the internal and external degrees of freedom of the protein and ligand, there is no simple way to calculate the free energy of releasing the noninteracting ligand to the standard state.…”
Section: Introductionmentioning
confidence: 99%
“…Free energy perturbation (FEP) molecular dynamics simulations were conducted according to the Streamlined Alchemical Free Energy Perturbation (SAFEP) methodology, described in detail in (21). We followed the set-up and analysis procedure described in (20). Briefly, SAFEP uses a limited set of restraints on the ligand to maintain its bound conformation during alchemical transformations and improve sampling of states that most contribute to the binding free energy.…”
Section: Methodsmentioning
confidence: 99%
“…From the dose response curve for ryanodine we found that 1 µM ryanodine resulted in the maximum Fura-2 340:380 nm ratio, and as a result this concentration was used to determine the inhibition, if any, caused by different concentrations of propofol. The various propofol concentrations (2,5,10,20,50,100,200, 300 µM) was added to 1µM ryanodine. The 340/380 nm ratios were measured using the same method in Experiment 1.…”
Section: Ryr1 Proteolipsome Reconstitutionmentioning
confidence: 99%
See 1 more Smart Citation